(untitled) (Research, Society and Development, 2022)
Background: Meteorological variables play a major role in the transmission of infectious diseases such as coronavirus disease 2019 (COVID-19). Objective: To analyze the correlation between climatic variables and COVID-19 deaths/cases. Methods: An exploratory-descriptive study based on secondary data on deaths, cases of COVID-19 and climatic variables from March 2020-May 2021 in Fortaleza, Brazil. Data from the COVID-19 surveillance system of the Ministry of Health were used. The climatic indicators were extracted from the National Institute of Meteorology. The variables under study were temperature (minimum, mean and maximum in °C), relative air humidity (%), total precipitation (mm) and total daily insolation (h). Pearson’s correlation and the linear regression model were used for statistical analysis. Correlations were considered significant when P ≤ 0.05 and a 95% confidence interval was adopted. Results: All meteorologic variables were correlated with deaths from COVID-19, temperature minimum (r = -0,126; P < 0,01), mean temperature (r = -0,146; P < 0,05), maximum temperature (r = -0,190; P < 0,001), insolation (r = -0,214; P < 0,001), precipitation (r = 0,216; P < 0,001) and relative humidity (r = 0,348; P < 0,001). In relation to the new cases of COVID-19, only maximum temperature (r = -0,116; P < 0,05), insolation (r = -0,141; P < 0,01) and relative humidity (r = 0,231; P < 0,001) were correlated are significantly. Conclusion: There were significant correlations between meteorological variables and COVID-19 deaths/cases. It was found that meteorologic variables had the most influence on COVID-19 deaths.